Doravirine-associated resistance mutations in antiretroviral therapy naïve and experienced adults with HIV-1 subtype C infection in Botswana. (December 2022) - Bareng, Ontlametse T.; Seselamarumo, Sekgabo; Seatla, Kaelo K.; Choga, Wonderful T.; Bakae, Blessing; Maruapula, Dorcas; Kelentse, Nametso; Moraka, Natasha O.; Mokaleng, Baitshepi; Mokgethi, Patrick T.; Ditlhako, Tsotlhe R.; Pretorius-Holme, Molly; et al.
Highlights: Lower DOR-resistance in ART-naïve versus ART-experienced individuals with VF. DOR-resistance was higher among individuals failing NNRTI-containing regimens. DOR use in NNRTI-experienced population should be based on HIV drug resistance data. ABSTRACT: Objectives: There are limited data on the prevalence of doravirine (DOR)-associated drug resistance mutations in people with HIV (PWH) in Botswana. This cross-sectional, retrospective study aimed to explore the prevalence of DOR-associated resistance mutations among ART-naïve and -experienced PWH in Botswana enrolled in the population-based Botswana Combination Prevention Project (BCPP). Methods: A total of 6078 HIV-1C pol sequences were analysed for DOR-associated resistance mutations using the Stanford HIV drug resistance database, and their levels were predicted according to the Stanford DRM penalty scores and resistance interpretation. Virologic failure was defined as HIV-1 RNA load (VL) >400 copies/mL. Results: Among 6078 PWH, 5999 (99%) had known ART status, and 4529/5999 (79%) were on ART at time of sampling. The suppression rate among ART-experienced was 4517/4729 (96%). The overall prevalence of any DOR-associated resistance mutations was 181/1473 (12.3% [95% confidence interval CI: 10.7–14.1]); by ART status: 42/212 (19.8% [95% CI: 14.7–25.4]) among ART-failing individuals (VL ≥400 copies/mL) and 139/1261 (11.0% [95% CI: 9.3–12.9]) among ART-naïve individuals ( P < 0.01). Intermediate DOR-associated resistance mutations were observed in 106/1261 (7.8% [95% CI: 6.9–10.1]) in ART-naïve individuals and 29/212 (13.7% [95% CI: 9.4–8.5]) among ART-experienced participants ( P < 0.01). High-level DOR-associated resistance mutations were observed in 33/1261 (2.6% [95% CI: 1.8–3.7]) among ART-naïve and 13/212 (6.1% [95% CI: 3.6–10.8]) among ART-failing PWH ( P < 0.01). PWH failing ART with at least one EFV/NVP-associated resistance mutation had high prevalence 13/67 (19.4%) of high-level DOR-associated resistance mutations. Conclusion: DOR-associated mutations were rare (11.0%) among ART-naive PWH but present in 62.7% of Botswana individuals who failed NNRTI-based ART with at least one EFV/NVP-associated resistance mutation. Testing for HIV drug resistance should underpin the use of DOR in PWH who have taken first-generation NNRTIs.